Glimpsing the Future: Expectations for Tomorrow’s Workplaces - Ramos, S.; Velez, M. J.; Silva, S.A.; Torres, D.; Molek, N.; van Biezen, A.; Pulinx, R. (22nd Congress of the European Association of Work and Organizational Psychology (EAWOP), 2025)
Academics, practitioners, and policymakers widely recognize that several megatrends are transforming today’s world of work and shaping the tomorrow’s work. Key drivers include demographic changes (e.g., aging populations, migration flows), technological advancements (e.g., automation, artificial intelligence, robotics), climate change, and the green transition – undeniable forces influencing work at multiple levels: the labour market (employment and unemployment dynamics, labour shortages, active population composition), organizations (innovation, decarbonization, new required skills), jobs (job extinction and new job opportunities, technological interfaces), and working conditions (digitalization, flexible work arrangements, emerging risks). These dynamics generate interconnected and complex impacts on workforce profiles, requiring a comprehensive approach to prepare both organizations and workers for forthcoming challenges. Moreover, these impacts vary significantly across markets, economic sectors, and countries. The CERV TRANSFORM project – “The Future of Human Workforce: Embracing Change, Challenges, and Opportunities” – aims to explore and address critical aspects of future workforce development. Supported by the European Union, the project unites researchers and experts from nine Member States (Belgium, Germany, Greece, Italy, Malta, Poland, Portugal, Slovenia, and Sweden). Through data collection across multiple European countries, the project seeks to understand how citizens, particularly workers, perceive these transformative trends.